2017
DOI: 10.3892/etm.2017.4142
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated protein kinase mediates the effects of lipoprotein-associated phospholipase A2 on endothelial dysfunction in atherosclerosis

Abstract: The present study aimed to investigate the effects of lipoprotein-associated phospholipase A2 (Lp-PLA2) on endothelial dysfunction in an cell model of atherosclerosis, and to determine whether AMP-activated protein kinase (AMPK) mediates the effects of Lp-PLA2 on endothelial dysfunction. A total of 392 patients with coronary artery disease (CAD), including various sub-conditions, were recruited, and the plasma concentrations of Lp-PLA2 were evaluated. In addition, an model of atherosclerosis was established by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…The AMPKα isoform is mainly expressed in VSMCs (Cai et al, 2016;Song et al, 2011), cardiomyocytes (X. and adipocytes (Sun et al, 2017). Recent evidence indicated that the activation of AMPKα stabilizes atherosclerotic plaque (Liang et al, 2018;Ma et al, 2018;L. Yang, Cong, Wang, & Liu, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The AMPKα isoform is mainly expressed in VSMCs (Cai et al, 2016;Song et al, 2011), cardiomyocytes (X. and adipocytes (Sun et al, 2017). Recent evidence indicated that the activation of AMPKα stabilizes atherosclerotic plaque (Liang et al, 2018;Ma et al, 2018;L. Yang, Cong, Wang, & Liu, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…AA is increased in the circulation, kidney, and urine with HFD in our study and this is consistent with increased circulating PUFA's demonstrated with HFD feeding in Sprague-Dawley rats (40). In excess nutrient states, phospholipase D suppresses AMPK activity through the mammalian/mechanistic target of rapamycin (mTOR); in return, AMPK activation decreased phospholipase D activity similar to the effect of AMPK activation on other phospholipases in vascular smooth muscles, and endothelial cells (19,41,42). Thus, the effect of AMPK activation on phospholipases in our study could be responsible for the changes to the PUFA levels with AICAR therapy.…”
Section: Pufa's Are Unaffected By Hfd or Ampk Activation In Our Studysupporting
confidence: 58%
“…NO is a multifunctional signaling molecule produced by HVECs and is involved in the maintenance of metabolic and cardiovascular homeostasis. NO is also a potent endogenous vasodilator associated with key processes that suppress the formation of vascular lesions [35] and protects against atherosclerosis by inhibiting oxidation, scavenging free radicals, inhibiting the oxidation of lowdensity lipoprotein (LDL) in blood vessels, preventing the production of oxidized LDL (Ox-LDL), inhibiting the activation of nuclear factor κB (NF-κB) [36], preventing abnormal constriction (vasospasm) of coronary arteries etc. NO also inhibits the infiltration and adhesion of white blood cells (macrophages) [37].…”
Section: Nitric Oxide (No)mentioning
confidence: 99%